Antibacterial Activity From Goat’s Milk Whey Hydrolized by Protease Enzyme of Bacillus Lincheniformis - Irma Isnafia Arief; Sitta Fitri Rahmadhina; Cahyo Budiman (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2023)
Food additives had been used to prevent and inhibit the growth of microorganisms and extend shelf life of food. Based on the safety of their used, it has an impact such as microorganism resistance to synthetic antimicrobials. This encourages the development of antimicrobials derived from natural ingredients, especially from milk. The bioactive components of milk protein have not always existed in their natural state, including precursors or peptides that will only be active if they have been hydrolyzed in vitro from their natural proteins. Hydrolysis of milk protein can be carried out using proteolytic enzymes from various sources, including protease extracted from Bacillus lincheniformis. This study used different concentrations of the protease extracted from Bacillus lincheniformis (0.5%, 1% and 1.5%) to produce hydrolyzate which has antibacterial activity in terms of protein content, SDS PAGE profile and the size of the inhibition zone (disc method). The results showed that the best activity of the whey hydrolyzed on Gram-negative Escherichia coli was 1% concentration of protease enzyme. In comparison, Gram positive Staphylococcus aureus can be inhibited with 0.5% concentration of protease enzyme.